Heterocyclic Compounds Bearing Triazine Scaffold and Their Biological Significance: A Review - Verma, Tarawanti; Sinha, Manish; Bansal, Nitin (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Benzene is a six-membered hydrocarbon ring system and if three carbon-hydrogen units of benzene ring are replaced by nitrogen atoms then triazine is formed. Triazines are present in three isomeric forms 1,2,3- triazine, 1,2,4-triazine, and 1,3,5-triazine according to the position of the nitrogen atom. These are weak bases having weaker resonance energy than benzene, so nucleophilic substitution is preferred than electrophilic substitution. Triazine is an interesting class of heterocyclic compounds in medicinal chemistry. Numerous synthetic derivatives of triazine have been prepared and evaluated for a wide spectrum of biological activities in different models with desired findings such as antibacterial, antifungal, anti-cancer, antiviral, antimalarial, antiinflammatory, antiulcer, anticonvulsant, antimicrobial, insecticidal and herbicidal agents. Triazine analogs have exposed potent pharmacological activity. So, triazine nucleus may be considered as an interesting core moiety for researchers for the development of future drugs.
Keywords: anticonvulsant